The Effectiveness of Ginger Rhizome Extract to Inhibit the Growth of Sclerotium rolfsii in Peanut In-vitro: Potensi Ekstrak Rimpang Jahe dalam Menghambat Pertumbuhan Sclerotium rolfsii pada Kacang Tanah secara In Vitro - Syafitri, Syafitri; Sulyanti, Eri; Arneti, Arneti; Swandi, Fradilla (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2022)
Sclerotium rolfsii is a fungus that causes stem rot disease in peanuts which causes losses of up to 59%. One technique of controlling the S. rolfsii is using a botanical fungicide, such as ginger (Zingiber officinale Rosc.) rhizome extract. This study aimed to determine the proper concentration of ginger rhizome extract to control S.rolfsii, the causes of stem rot, and damping-off diseases in peanut in-vitro. This study used a completely randomized design with five treatments and five replications. The treatments were arranged in the concentration of 0, 4%, 6%, 8%, and 10% by in-vitro. The data were analyzed using ANOVA, followed by an LSD of 5%. The results showed that ginger rhizome extract could suppress the growth of S. rolfsii, which causes stem rot disease in peanut plants. Ginger rhizome extract reduced the thickness of the colonies, suppressed colony expansion, reduced the wet and dry weight of the colonies, slowed the appearance of Sclerotia, and reduced the number of Sclerotia formed. The higher concentration, the higher the emphasis on S. rolfsii. Ginger rhizome extract at a concentration of 10% can inhibit colony growth by 81.63%, inhibit the formation of sclerotia by 100%, reduce the wet weight of the colony to 66.88% and the dry weight of the colony to 44.11% and inhibit the formation of Sclerotia reaching 100%.